Crisis of Humanity in Human–Nature Relations in Seno Gumira Ajidarma’s Macan - Rosita Sofyaningrun; Rudi Rudi (Metafora: Education, Social Sciences and Humanities Journal, 2026)
Abstract The short story Macan by Seno Gumira Ajidarma presents a sharp critique of human behavior that often disrupts environmental balance and disregards harmonious relationships with nature. This study aims to analyze the conflict between humans and nature depicted in the short story through an ecocritical approach. The primary focus of the research is on human dominance over nature, criticism of environmentally destructive behavior, and its impact on raising awareness and changing societal attitudes toward human-environment relationships. A descriptive-qualitative method is employed to explore representations of human-nature conflict, human dominance, and the symbolism contained in the story. Text analysis and literature review reveal how Macan portrays injustice, indifference, and human domination over the environment, both through physical conflicts such as wildlife hunting and symbolic elements reflecting nature’s attempts to maintain balance. The ecocritical critique in this short story highlights the negative impacts of human activities on the environment, the importance of moral reflection, and the need for ecological responsibility. This study not only enriches ecocritical literary studies in Indonesia but also encourages societal behavioral change toward more environmentally friendly practices through the reflections presented in this literary work. Keywords: Macan, Ecocritics, Human, Nature, Crisis Abstrak Cerita pendek Macan karya Seno Gumira Ajidarma menyajikan kritik tajam terhadap perilaku manusia yang kerap merusak keseimbangan lingkungan dan mengabaikan hubungan harmonis dengan alam. Penelitian ini bertujuan untuk menganalisis konflik antara manusia dan alam yang digambarkan dalam cerita pendek tersebut melalui pendekatan ekokritik. Fokus utama penelitian ini adalah pada dominasi manusia terhadap alam, kritik terhadap perilaku perusakan lingkungan, serta dampaknya dalam meningkatkan kesadaran dan mengubah sikap masyarakat terhadap hubungan manusia–lingkungan. Metode deskriptif kualitatif digunakan untuk menggali representasi konflik manusia–alam, dominasi manusia, dan simbolisme yang terkandung dalam cerita. Analisis teks dan kajian pustaka menunjukkan bagaimana Macan menggambarkan ketidakadilan, ketidakpedulian, dan dominasi manusia atas lingkungan, baik melalui konflik fisik seperti perburuan satwa liar maupun unsur simbolik yang mencerminkan upaya alam mempertahankan keseimbangan. Kritik ekokritik dalam cerita pendek ini menyoroti dampak negatif aktivitas manusia terhadap lingkungan, pentingnya refleksi moral, dan perlunya tanggung jawab ekologis. Penelitian ini tidak hanya memperkaya kajian sastra ekokritik di Indonesia, tetapi juga mendorong perubahan perilaku masyarakat menuju praktik yang lebih ramah lingkungan melalui refleksi yang disampaikan dalam karya sastra tersebut. Kata Kunci: Macan, Ekokritik, Manusia, Alam, Krisis